The perfect gentleman : the pursuit of timeless elegance and style in London - Sherwood, James (London : Thames & Hudson, 2012)
- Monarchy, gallantry & debauchery : Restoration London (1666-1789)##- Fashion, revolution & aspiration : Regency London (1789-1837)##- Empire, affluence & ingenuity : Victorian London (1837-1880)##- Pleasure, excess & ostentation : Edwardian London (1880-1914)##- Modernism, frivolity & chic : London between two wars (1914-1940)##- Austerity, optimism & energy : London's new Elizabethan Age (1940-present)##- Epilogue##- The perfect gentleman's London landscape.
boek